The free cash flow on profitability: effect on food processor company listed in Bursa Malaysia / Wan Raimi Afsham Mohd Shukor - Mohd Shukor, Wan Raimi Afsham (2018)
The discourse objective of the study is to investigate the relationship between The Free Cash Flow on Profitability on Food Processor Company Listed in Bursa Malaysia. This study adopted panel data as the method of the study. The population consisted of Food Processor Company listed in Bursa Malaysia as at 2018. The sample of seventy one (71) companies was chosen with the main criteria of at least 10 years history in Bursa Malaysia. This means that company that listed after 2007 was not chosen in this study. Secondary data was extracted from companies annual report and financial statement sourced from data stream from the period of 10 years (20082017). There are 3 independent variables involve in this study which are free cash flow, capital liquidity and leverage. The dependent variable for this test is food processor Company's profitability. Based on regression result, it was found that the squared is 0.184425. The independent variables show 18.4425 percent variation of profitability on Food Processor Company Listed in Bursa Malaysia. All the independent variable show significant value. Based on the T-test result, all three independent variable show significant value where the result is less than 1% significant level as shown on table 4.3 in chapter 4. The result is consistent with the study conduct by Akumu (2014) where free cash flow show positive and significant impact on profitability of Finns Listed on The Nairobi Securities Exchange.